2020
DOI: 10.1093/scan/nsaa066
|View full text |Cite
|
Sign up to set email alerts
|

Mind the social feedback: effects of tDCS applied to the left DLPFC on psychophysiological responses during the anticipation and reception of social evaluations

Abstract: Abstract The left dorsolateral prefrontal cortex (lDLPFC) is implicated in anticipatory (i.e. during anticipation of emotional stimuli) and online (i.e. during confrontation with emotional stimuli) emotion regulatory processes. However, research that investigates the causal role of the lDLPFC in these processes is lacking. In this study, 74 participants received active or sham transcranial direct current stimulation (tDCS) over the lDLPFC. Participants were told … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 81 publications
1
22
0
Order By: Relevance
“…This estimated a total sample size of N = 74 to detect with 80% power the hypothesized betweenwithin interaction effect of a small to moderate magnitude (Cohen's f = 0.15) using a mixed ANOVA F-test. Participants were recruited in the context of a larger research project investigating the effects of left prefrontal tDCS on the interplay between anticipatory and online emotion regulatory processes to social evaluations (Allaert et al, 2020). They were recruited from the general community via internet postings on social media and posters in public places.…”
Section: Participantsmentioning
confidence: 99%
See 4 more Smart Citations
“…This estimated a total sample size of N = 74 to detect with 80% power the hypothesized betweenwithin interaction effect of a small to moderate magnitude (Cohen's f = 0.15) using a mixed ANOVA F-test. Participants were recruited in the context of a larger research project investigating the effects of left prefrontal tDCS on the interplay between anticipatory and online emotion regulatory processes to social evaluations (Allaert et al, 2020). They were recruited from the general community via internet postings on social media and posters in public places.…”
Section: Participantsmentioning
confidence: 99%
“…First, based on the self-regulation theories proposing adaptive SET reactivity consists of both decreased self-attention and increased otherattention (Hess and Pickett, 2010;Durlik and Tsakiris, 2015), and given the wide array of research showing adaptive left prefrontal tDCS effects on attention processes and emotional reactivity (Mondino et al, 2015;Smits et al, 2020), we expected that active (in contrast to sham) left prefrontal tDCS would be associated with attenuated self-attention (i.e., slower first fixation to and less total fixation time on this information) and increased other-attention (i.e., faster first fixation to and more total fixation time on this information). We had no clear expectations whether these effects would be modulated by valence, as previous prefrontal tDCS research has shown both valence-independent (Sanchez-Lopez et al, 2018;Allaert et al, 2020), and valence-dependent tDCS effects (Mondino et al, 2015;Nejati et al, 2021). Second, based on the proposed association between prefrontal-mediated attentional processes and emotional reactivity, we expected the attentional processes that are modulated by tDCS to be more strongly associated with attenuated emotional reactivity (assessed via SCRs) among participants receiving active (versus sham) tDCS.…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations